Analisis Persiapan PT. Bank Pembiayaan Rakyat Syariah Al Makmur dalam Penerapan Good Corporate Governance - Hendra Putra; Zainuddin Zainuddin; Alimin Alimin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The aim is to analyze the preparation of PT. Bank Pembiayaan Rakyat Syariah Al Makmur in implementing Good Corporate Governance (GCG) in the Awareness Building, GCG Assessment and Manual Building stages. The method used is descriptive qualitative, the data collection technique used by the writer is through interviews and documentation, Data processing was carried out by qualitative analysis then presented the data in a short narrative description, then analyzed and concluded. The Awareness Building stage has been done well, but it must be maximized more by providing education through seminars, workshops and group discussions sustainably. So that, all elements that involved have the same understanding and awareness of the importance of implementing GCG. For the GCG Assessment stage which carried out by the internal company is in accordance, but in determining the priority scale must pay attention to the internal conditions of the company. And for the Manual Building stage (preparation of guidelines) of PT. PT. Bank Pembiayaan Rakyat Syariah Al-Makmur has not completed the GCG